Determination Of Factors That Can Improve Employee Performance - Agustiana, Gian; garnida, faizal; dwi putra, reynaldi; rudiantono, yodi (CV. AFDIFAL MAJU BERKAH, 2024)
Organizational Citizenship Behavior and Organizational Commitment are critical factors in improving employee performance and overall organizational effectiveness. OCB refers to voluntary, extra-role behaviors that contribute to organizational efficiency and social environment, while Organizational Commitment reflects the psychological attachment and loyalty of employees to their organization. This research focuses on the interplay between these variables and their combined effect on employee performance. This study aims to evaluate the effects of organizational commitment and organizational citizenship behavior (OCB) on worker performance. Associative research was the methodology employed in this study. The 108 employees or former employees of PT PG Rajawali II make up the study's population. Multiple linear regression was used by the analytical tool. The results showed that organizational commitment and organizational citizenship behavior (OCB) have an impact on worker performance at PT PG Rajawali II. Multiple linear regressin result is Y= 1.239 + 0.235 X1 + 0.71 X2 Employee performance can be enhanced for the benefit of the company and the individual by staff members who possess OCB and organizational commitment. To boost staff performance, PT PG Rajawali II should uphold and enhance the standard of corporate commitment and citizenship conduct.